The impact of internet access on COVID-19 spread in Indonesia - Johannes Kunz; Carol Propper; Trong-Anh Trinh (Asian Development Bank (ADB), 2024)
The coronavirus disease (COVID-19) pandemic has highlighted the crucial role of Internet access in pandemic prevention and response. Internet access has facilitated the rapid dissemination of vital information, provided telemedicine services, and enabled remote work and education. This study uses a wide range of data sources to investigate the geographic variation of Internet access proxied by 3G mobile broadband during the COVID-19 pandemic in Indonesia. We employ several approaches to account for potential confounding factors, including using lightning strikes as an instrumental variable, to confirm the significant role that the Internet played in the spread of COVID-19 cases. Our findings suggest that increasing Internet access could positively impact pandemic prevention and response efforts, particularly in regions with limited connectivity. Therefore, improving Internet infrastructure in developing countries may be crucial in preventing future pandemics.
Keywords: I12; I15; I31; O18; L96; H41; 330; health emergencies; Internet access; information; COVID-19 spread